2018
DOI: 10.1088/1361-6587/aabd10
|View full text |Cite
|
Sign up to set email alerts
|

Quasi-monoenergetic multi-GeV electron acceleration by optimizing the spatial and spectral phases of PW laser pulses

Abstract: Generation of high-quality electron beams from laser wakefield acceleration requires optimization of initial experimental parameters. We present here the dependence of accelerated electron beams on the temporal profile of a driving PW laser, the density, and length of an interacting medium. We have optimized the initial parameters to obtain 2.8 GeV quasimonoenergetic electrons which can be applied further to the development of compact electron accelerators and radiations sources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 45 publications
5
11
0
Order By: Relevance
“…These observations are broadly consistent with the results of Kim et al, who found that applying a positive second-order phase and a negative third-order phase increased the performance of a wakefield accelerator driven by a petawatt laser [38,39]. The key advance made in this work is that both parameters are optimized simultaneously, which is necessary when the optimal value of the secondorder phase at zero third-order phase differs from the globally optimal value.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These observations are broadly consistent with the results of Kim et al, who found that applying a positive second-order phase and a negative third-order phase increased the performance of a wakefield accelerator driven by a petawatt laser [38,39]. The key advance made in this work is that both parameters are optimized simultaneously, which is necessary when the optimal value of the secondorder phase at zero third-order phase differs from the globally optimal value.…”
Section: Discussionsupporting
confidence: 91%
“…Despite operating in a very different regime, the optimal pulse shape is similar to the one found by Kim et al, having a slow-rising edge and a fast-falling edge. Their conclusion, supported by particle-in-cell (PIC) simulations, was that this shape significantly reduced the amount of selfmodulation suffered by the laser pulse [38,39]. This led to a more stable acceleration process, maintained over a longer distance.…”
Section: A Pulse Shapesmentioning
confidence: 89%
“…A robust scheme for controlling the properties of multi-GeV electron beams is based on the adjustment of the spectral phase of the laser pulse. Such results were investigated experimentally [58,86], and the works showed that energy, charge, and stability of the electron beams can be improved by adjusting the group delay dispersion (GDD) and third-order dispersion (TOD) of the spectral phase.…”
Section: Experimental Investigation Of Laser Wakefield Accelerationmentioning
confidence: 99%
“…In the dual-stage acceleration, the PW laser pulse was stretched to be positively chirped with a duration of 60 fs. It was stretched to control the acceleration gradient of LWFA by manipulating the pulse's spectral phase [32]; such a control method was demonstrated experimentally at UQBF [13,33]. In particular, positive group-delay dispersion (GDD) enhanced the energy and charge of the electron beam, and third-order dispersion (TOD) improved the energy further and the stability of the beams.…”
Section: Dual-stage Lwfa With Pw Laser At Uqbfmentioning
confidence: 99%
“…It can contain high-intensity laser pulses in the relativistic regime due to the extremely high-intensity limit of the plasma medium. Several groups developed plasma channel technology [34][35][36], and the research group at Lawrence Berkley National Laboratory successfully applied the plasma channel to enhance the electron energy [16,32,33].…”
Section: Lwfa With Capillary Discharge Plasmas At Lbnlmentioning
confidence: 99%